Two Sides of the Same Coin—Mechanistic Insight, Diagnostic Application and Therapeutic Translation of Bacterial and Host-Derived Extracellular Vesicles - Arnold, Philipp; Boros, Fanni Annamaria; Mattner, Jochen; Seidel, Gerald; Liu, Chaofan; Hensel, Inga; Van Deun, Jan; Schwendner, Raphael; Müller-Deile, Janina; Sopel, Nina; Ramming, Andreas; Angeli, Mario Raphael; et al. (Journal of Extracellular Biology, 2025)
Extracellular vesicles (EVs) have gained increasing attention in recent years due to their pivotal role in both health and disease. Emerging from both eukaryotic and prokaryotic cells, EVs serve as essential mediators of intercellular communication, exceeding the simplistic interactions observed with individual molecules. In this comprehensive review, we will focus on both Bacterial Extracellular Vesicles (BEV) and on Host derived Extracellular Vesicles (HEV) and highlight mechanistic principles, as well as their transformation into diagnostic and therapeutic tools. We will start with a short introduction into the biogenesis and principal properties of BEV and HEV. We will then focus on the composition of BEV and introduce OMICs-based studies that helped to unravel their complex constitution. As both BEV and HEV interact with different epithelial and endothelial barriers and shape their properties, we will highlight mechanistic principles for both EV types. Starting from the intestinal system, where we will look at BEV and how these BEV overcome the intestinal barrier to change distant organs and the patient's immune system. We will then visit other endothelial and epithelial sites of the human body and summarize how HEV shapes these barriers and how HEV can overcome these barriers. We will then turn towards diagnostic and therapeutic approaches. As both BEV and HEV are currently suggested as diagnostic markers and are being investigated as potential therapeutic agents. Lastly, we will discuss current challenges and provide an outlook on the future in the field. This review seeks to raise awareness for both bacterial and host-derived EVs, highlighting that they present two sides of the same coin.
CRIS-Team Scopus Importer:2025-11-07